Expression Status and Prognostic Significance of Gamma-Glutamyl Transpeptidase Family Genes in Hepatocellular Carcinoma - Tian, Shan; Li, Jiao; Guo, Yingyun; Dong, Weiguo; Zheng, Xin (Frontiers in Oncology, 2021)
Purpose: Gamma-glutamyl transpeptidase (GGT) family genes play crucial roles in the tumor formation and progression of several solid tumors. However, the expression patterns and prognostic significance of GGT members in hepatocellular carcinoma (HCC) remains unknown. This study was designed to determine the expression profiles of GGT family members in HCC, and validate the prognostic value of serum GGT protein in HCC patients. Method: We comprehensively searched public resources based on LIHC dataset to probe into the expression patterns, prognostic significance, DNA methylation status, immune infiltration and biological pathways of GGT family genes in HCC. Subsequently, we also validated the prognostic value of serum GGT protein in 85 early-stage HCC patients with curative hepatectomy based on the Renmin Hospital of Wuhan University. Results: Except for GGT1, other GGT family members (GGT5, GGT6 and GGT7) were found to be differentially expressed in primary HCC samples (N=371) and normal control tissues (N=50). The positive relationship was not only observed between GGT1 and GGT5 (Spearman coefficient: 0.24, P=5.143×10-6)，but also between GGT5 and GGT6 (Spearman coefficient: 0.38, P=1.24×10-13). Expressions of GGT1, GGT5 and GGT7 were correlated with overall survival (OS)，and GGT7 was associated with disease-free survival (DFS) in HCC patients. Negative associations between DNA methylation and expression of mRNA were observed in GGT1 (Spearman coefficient: -0.38, P=6.24e-14), GGT6 (Spearman coefficient: -0.29, P=1.23e-8) and GGT7 (Spearman coefficient: -0.34, P=6.7e-11). GGT family genes were well correlated with the infiltration levels of immune cells in HCC, especially CD4+ T cells, macrophages and dentric cells. Finally, when validated with clinical data from Renmin cohort, high expression of serum GGT protein was a strong prognostic element for unfavorable OS (HR=3.114, P=0.025), while not for DFS (HR=1.198, P=0.05) in HCC patients with curative hepatectomy. Conclusion: This is the first comprehensive analysis of the expression patterns and clinical values of GGT family genes in patients with HCC. Our study laid foundation for the clinical application of GGT protein in the survival assessment of HCC patients.